Double-sided pressure-sensitive adhesive tape
By using a polyurethane-based resin base layer and a pressure-sensitive adhesive layer with high content butyl methacrylate in a double-sided pressure-sensitive adhesive tape, combined with a crosslinker and a tackifying resin, the impact resistance in the prior art is solved. The problem of insufficient properties, reprocessability and alcohol resistance achieves efficient bonding and stability of electronic device components in mobile devices.
Patent Information
- Application Number
- CN202011508382.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-12-18
AI Technical Summary
The existing double-sided pressure-sensitive adhesive tape has shortcomings in impact resistance, reprocessability and alcohol resistance, especially when used in mobile devices, and the adhesive strength to the adhered is insufficient, making it difficult to satisfy. High impact resistance and high alcohol resistance requirements.
A combined structure of a base layer and a pressure-sensitive adhesive layer is adopted, wherein the base layer is formed of a polyurethane resin, and the pressure-sensitive adhesive layer contains more than 50 wt% butyl methacrylate, through polymer components and monomers. The combination of components forms a double-sided pressure-sensitive adhesive tape at 100% strain and the force generated is between 30N/m and 150N/m, ensuring impact resistance and reprocessing properties, and improving through crosslinking agents and tackifying resins. Alcohol resistance.
The double-sided pressure-sensitive adhesive tape is realized to show excellent impact resistance, reprocessing and alcohol resistance in the mobile device, ensuring high bonding strength and stability to the adhered, and is suitable for fixing electronic device components. .
Smart Images

Figure CN113004836B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a double-sided pressure-sensitive adhesive tape. Background Art
[0002] In recent years, with the trend of diversification of various performances of mobile devices, diversification of various performances of various constituent members used in mobile devices has been required. In mobile devices, double-sided pressure-sensitive adhesive tapes are sometimes used for joining housings, etc. In recent years, diversification of various performances of double-sided pressure-sensitive adhesive tapes has also been required.
[0003] There is a risk that the mobile device falls depending on its usage form. Therefore, a mobile device having high impact resistance has been required. A shock absorbing member is sometimes configured outside the housing of the mobile device for improving the impact resistance of the mobile device. However, in such a form, the size of the mobile device increases or its designability is impaired.
[0004] In view of the foregoing, it is desirable that excellent impact resistance be imparted to a double-sided pressure-sensitive adhesive tape that can be disposed in a mobile device.
[0005] Recently, a double-sided pressure-sensitive adhesive sheet with impact resistance has been reported (Japanese Patent Application Laid-Open No. 2015-120876). The double-sided pressure-sensitive adhesive sheet includes a substrate made of a foam as an essential component to exhibit impact resistance. However, when the foam is extended to a certain extent or a force is applied thereto, the foam tears and has a smaller area or becomes thinner. As a result, there is a problem in that the cell portion of the foam occupies the majority of the bonding portion between the sheet and the adherend, thereby reducing the adhesion therebetween.
[0006] Furthermore, double-sided pressure-sensitive adhesive sheets to be used in mobile devices are often attached to expensive components, and therefore are required to have satisfactory reworkability at the time of re-attachment, etc. However, double-sided pressure-sensitive adhesive sheets of the prior art cause problems such as tearing during rework, and double-sided pressure-sensitive adhesive sheets to be used in mobile devices are required to have excellent reworkability.
[0007] In addition, mobile devices are often exposed to daily living environments and often come into contact with alcohol-based solutions such as cleaning solutions or disinfectants.
[0008] Therefore, the pressure-sensitive adhesive sheet to be used for mobile devices is required to have all of high adhesive strength, high impact resistance and high alcohol resistance to various adherends that can be used for mobile devices. However, the pressure-sensitive adhesive sheet of the prior art cannot achieve all of these properties alone, so there is a demand for a technology that can show all of high adhesive strength, high impact resistance and high alcohol resistance to various adherends that can be used for mobile devices. Summary of the invention
[0009] An object of the present invention is to provide a double-sided pressure-sensitive adhesive tape which can exhibit all of excellent impact resistance, excellent reworkability, and excellent alcohol resistance.
[0010] According to at least one embodiment of the present invention, there is provided a double-sided pressure-sensitive adhesive tape comprising: a substrate layer; and pressure-sensitive adhesive layers arranged on both sides of the substrate layer, wherein the pressure-sensitive adhesive layers are each formed of a pressure-sensitive adhesive composition, wherein the pressure-sensitive adhesive composition comprises at least one selected from the group consisting of a monomer component (m) and a polymer component (P) obtained by polymerizing the monomer component (m), wherein the monomer component (m) comprises 50 wt % or more of butyl (meth)acrylate, wherein the ratio of the thickness of the substrate layer to the total thickness of the double-sided pressure-sensitive adhesive tape is less than 35%, and wherein the force generated by the double-sided pressure-sensitive adhesive tape at 100% strain at 23° C. and 50% RH is 30 N / m to 150 N / m.
[0011] In at least one embodiment of the present invention, the substrate layer is formed of a resin film.
[0012] In at least one embodiment of the present invention, the resin film includes a polyurethane-based resin as a main component.
[0013] In at least one embodiment of the present invention, the monomer component (m) comprises 90 wt% to 99 wt% of butyl (meth)acrylate.
[0014] In at least one embodiment of the present invention, the monomer component (m) comprises 1 wt% to 10 wt% of (meth)acrylic acid.
[0015] In at least one embodiment of the present invention, the double-sided pressure-sensitive adhesive tape has a total thickness of 100 μm or more.
[0016] In at least one embodiment of the present invention, the double-sided pressure-sensitive adhesive tape is used to fix electronic device components. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a schematic cross-sectional view of a double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention. DETAILED DESCRIPTION
[0018] As used herein, the term “(meth)acryl” means at least one selected from the group consisting of acryl and methacryl, and the term “(meth)acrylate” means at least one selected from the group consisting of acrylate and methacrylate.
[0019] 《A. Double-sided pressure-sensitive adhesive tape》
[0020] The double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention comprises a substrate layer and a pressure-sensitive adhesive layer configured on both sides thereof. To the extent that the effect of the present invention is not impaired, the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention may include any appropriate other layer as long as the pressure-sensitive adhesive layer is configured on both sides of the substrate layer.
[0021] Figure 1 is a schematic cross-sectional view of a double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention. Figure 1 In the embodiment, the double-sided pressure-sensitive adhesive tape 100 includes a base material layer 10, and a pressure-sensitive adhesive layer 20a and a pressure-sensitive adhesive layer 20b on both sides thereof.
[0022] The pressure-sensitive adhesive layers may each be a single layer, or may include two or more layers.
[0023] The substrate layer may be a single layer, or may include two or more layers.
[0024] The total thickness of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention is preferably 100 μm or more because the effects of the present invention can be further exhibited, and is more preferably 100 to 1,000 μm, still more preferably 100 to 500 μm, particularly preferably 150 to 400 μm.
[0025] To the extent that the effect of the present invention is not impaired, any appropriate release liner may be arranged on the surface of the pressure-sensitive adhesive layer for, for example, protecting the tape until the tape is used. Examples of release liners include: a release liner obtained by subjecting the surface of a substrate (liner substrate) such as paper or a plastic film to a silicone treatment; and a release liner obtained by laminating a polyolefin-based resin on the surface of a substrate (liner substrate) such as paper or a plastic film. Examples of plastic films as liner substrates include polyethylene films, polypropylene films, polybutylene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films. The plastic film as the liner substrate is preferably a polyethylene film.
[0026] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, still more preferably 5 μm to 400 μm, particularly preferably 10 μm to 300 μm.
[0027] The force generated at 100% strain at 23°C and 50% RH of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention is 30 N / m to 150 N / m, preferably 30 N / m to 130 N / m, more preferably 30 N / m to 90 N / m, still more preferably 30 N / m to 80 N / m, and particularly preferably 32 N / m to 50 N / m. When the force generated at 100% strain is too low and falls outside the above range, there is a risk of problems such as a reduction in reprocessability, such as the double-sided pressure-sensitive adhesive tape being torn during reprocessing. When the force generated at 100% strain is too high and falls outside the above range, there is a risk that the impact resistance of the double-sided pressure-sensitive adhesive tape will be impaired.
[0028] The ratio of the thickness of the base material layer to the total thickness of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention is less than 35%, preferably 3% to 25%, more preferably 3% to 20%, still more preferably 3% to 15%, and particularly preferably 5% to 10%. When the ratio of the thickness of the base material layer to the total thickness of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention falls within the above range, the effects of the present invention can be fully exhibited.
[0029] The impact resistance of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention at 23°C and 50% RH is preferably 0.30 J or more, more preferably 0.34 J or more, still more preferably 0.39 J or more, still more preferably 0.44 J or more, particularly preferably 0.51 J or more, and most preferably 0.59 J or more. When the impact resistance is too low and falls outside the above range, there is a risk of not being able to provide a laminate that can exhibit high impact resistance.
[0030] The pressure-sensitive adhesive strength of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention is preferably 5 N / 10 mm to 50 N / 10 mm, more preferably 6 N / 10 mm to 40 N / 10 mm, still more preferably 7 N / 10 mm to 30 N / 10 mm, and particularly preferably 8 N / 10 mm to 20 N / 10 mm. When the pressure-sensitive adhesive strength of the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention falls within the above range, the function as a double-sided pressure-sensitive adhesive tape can be fully exhibited.
[0031] <A-1. Pressure-sensitive adhesive layer>
[0032] Each of the pressure-sensitive adhesive layers may be a single layer, or may include two or more layers. In the case of two or more layers, all of the pressure-sensitive adhesive layers may have the same composition, or at least one of the pressure-sensitive adhesive layers may be different in composition from the others.
[0033] Each of the pressure-sensitive adhesive layers is formed from a pressure-sensitive adhesive composition.
[0034] Each pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition by any suitable method. Examples of such methods include: a method (direct method) involving applying a pressure-sensitive adhesive composition, which is a forming material for the pressure-sensitive adhesive layer, onto any suitable substrate (e.g., a substrate film), and drying the composition as needed to form a pressure-sensitive adhesive layer on the substrate; and a method (transfer method) involving applying the pressure-sensitive adhesive composition onto a surface having peelability (peel surface), drying the composition as needed to form a pressure-sensitive adhesive layer on the surface having peelability (peel surface), and transferring the pressure-sensitive adhesive layer onto any suitable substrate (e.g., a substrate film). The surface having peelability (peel surface) is, for example, the surface of the release liner described above.
[0035] To the extent that the effects of the present invention are not impaired, any suitable coating method can be used as the method for applying the pressure-sensitive adhesive composition. Examples of such coating methods include roll coating, gravure coating, reverse coating, roll brushing, spraying, air knife coating method, and extrusion coating using a die coater or the like. Actinic ray irradiation such as UV irradiation can be performed for curing the coating layer formed by the application.
[0036] From the viewpoints of, for example, promoting the crosslinking reaction of the composition and improving the production efficiency of the tape, the drying of the pressure-sensitive adhesive composition can be carried out under heating. The drying temperature can typically be set, for example, to 40°C to 150°C, and preferably 60°C to 130°C. After drying the pressure-sensitive adhesive composition, for the purposes of, for example, regulating the migration of components in the pressure-sensitive adhesive layer, promoting the crosslinking reaction, and reducing the strain that may be present in the pressure-sensitive adhesive layer, further aging can be carried out.
[0037] The thickness of each pressure-sensitive adhesive layer is preferably 10 μm to 1,000 μm because the effects of the present invention can be further exhibited, and this thickness is more preferably 20 μm to 700 μm, still more preferably 30 μm to 500 μm, particularly preferably 40 μm to 300 μm, and most preferably 50 μm to 200 μm.
[0038] <A-1-1. Pressure-Sensitive Adhesive Composition>
[0039] The pressure-sensitive adhesive composition contains at least one selected from the group consisting of a monomer component (m) and a polymer component (P) obtained by polymerizing the monomer component (m). That is, typically, the pressure-sensitive adhesive composition can have any one of the following forms: a form (form 1) containing the polymer component (P) and substantially free of the monomer component (m); a form (form 2) containing the monomer component (m) and substantially free of the polymer component (P); and a form (form 3) containing both the monomer component (m) and the polymer component (P).
[0040] The form (form 1) containing the polymer component (P) and substantially containing no monomer component (m) is a form in which the polymer component (P) is substantially formed by polymerizing the monomer component (m) in the stage of preparing the pressure-sensitive adhesive composition.
[0041] The form containing the monomer component (m) and substantially not containing the polymer component (P) (form 2) is a form in which substantially no polymerization of the monomer component (m) occurs in the stage of preparing the pressure-sensitive adhesive composition, and thus the polymer component (P) has not yet been formed. In this form, the polymer component (P) can be formed by, for example, curing the applied layer formed by applying the prepared pressure-sensitive adhesive composition by irradiation with active energy rays such as UV irradiation.
[0042] The form (form 3) containing both the monomer component (m) and the polymer component (P) is a form in which, in the stage of preparing the pressure-sensitive adhesive composition, part of the molecules of the monomer component (m) are polymerized to form a part of the polymer, and the molecules of the unreacted monomer component (m) remain. In this form, the polymer component (P) can be formed by, for example, curing the applied layer formed by applying the prepared pressure-sensitive adhesive composition by irradiation with active energy rays such as UV irradiation.
[0043] In the case of form 1 (a form comprising a polymer component (P) and substantially free of a monomer component (m)), the content of the polymer component (P) in the pressure-sensitive adhesive composition is as follows: When the total amount of the pressure-sensitive adhesive composition is set to 100 parts by weight, the content of the polymer component (P) is preferably 50 wt % to 100 wt %, more preferably 60 wt % to 100 wt %, still more preferably 70 wt % to 100 wt %, and particularly preferably 80 wt % to 100 wt %.
[0044] In the case of form 2 (a form containing monomer component (m) and substantially free of polymer component (P)), the content of monomer component (m) in the pressure-sensitive adhesive composition is as follows: when the total amount of the pressure-sensitive adhesive composition is set to 100 parts by weight, the content of monomer component (m) is preferably 50 wt% to 100 wt%, more preferably 60 wt% to 100 wt%, still more preferably 70 wt% to 100 wt%, and particularly preferably 80 wt% to 100 wt%.
[0045] In the case of Form 3 (a form comprising both a monomer component (m) and a polymer component (P)), the total content of the polymer component (P) and the monomer component (m) in the pressure-sensitive adhesive composition is as follows: When the total amount of the pressure-sensitive adhesive composition is set to 100 parts by weight, the total content of the polymer component (P) and the monomer component (m) is preferably 50 wt% to 100 wt%, more preferably 60 wt% to 100 wt%, still more preferably 70 wt% to 100 wt%, and particularly preferably 80 wt% to 100 wt%.
[0046] The pressure-sensitive adhesive composition may contain any appropriate colorant to such an extent that the effects of the present invention are not impaired, from the viewpoint of, for example, adjusting its light transmittance (light-shielding property). Conventionally known pigments or dyes may be used as such a colorant. Examples of the pigment include: inorganic pigments such as carbon black, zinc carbonate, zinc oxide, zinc sulfide, talc, kaolin, calcium carbonate, titanium oxide, silicon dioxide, lithium fluoride, calcium fluoride, barium sulfate, aluminum oxide, zirconium oxide, iron oxide pigments, iron hydroxide pigments, chromium oxide pigments, spinel-type calcined pigments, chromic acid pigments, chrome vermilion pigments, iron blue pigments, aluminum powder pigments, bronze powder pigments, silver powder pigments, and calcium phosphate; and organic pigments such as phthalocyanine pigments, azo pigments, condensed azo pigments, azo lake pigments, anthraquinone pigments, perylene-pyrenone pigments, indigo pigments, thioindigo pigments, isoindolinone pigments, azomethine pigments, dioxazine pigments, quinacridone pigments, nigrosine pigments, and triphenylmethane pigments. Examples of the dye include azo dyes, anthraquinone, quinolones, styryl dyes, diphenylmethane, triphenylmethane, oxazine, triazine, xanthan gum, azomethine, acridine, and dioxazines. The colorant may be used alone or in combination thereof.
[0047] The black colorant is specifically, for example, carbon black, graphite, copper oxide, manganese dioxide, aniline black, perylene black, titanium black, cyanine black, activated carbon, ferrite (e.g., non-magnetic ferrite or magnetic ferrite), magnetite, chromium oxide, iron oxide, molybdenum disulfide, chromium complex or anthraquinone-based colorant.
[0048] The content of the colorant in the pressure-sensitive adhesive composition is preferably less than 30 wt %, more preferably less than 20 wt %, still more preferably less than 13 wt %, particularly preferably less than 10 wt %, most preferably less than 8 wt %.
[0049] To the extent that the effects of the present invention are not impaired, the pressure-sensitive adhesive composition may contain any suitable other components. Examples of such other components include resin components other than the polymer component (P), tackifiers, crosslinking agents, inorganic fillers, organic fillers, metal powders, pigments, foil-like substances, softeners, anti-aging agents, conductive agents, rust inhibitors, UV absorbers, antioxidants, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, and catalysts.
[0050] <A-1-1-1. Monomer component (m)>
[0051] The monomer component (m) contains 50 wt% or more of butyl (meth)acrylate. The content of butyl (meth)acrylate in the total amount of the monomer component (m) is preferably 50 wt% to 100 wt%, more preferably 70 wt% to 99.5 wt%, still more preferably 90 wt% to 99 wt%, particularly preferably 91 wt% to 98 wt%, and most preferably 92 wt% to 97 wt%. When the content of butyl (meth)acrylate in the monomer component (m) is adjusted within the above range, a double-sided pressure-sensitive adhesive tape can be provided that can exhibit all of excellent impact resistance, excellent reprocessability, and excellent alcohol resistance.
[0052] Butyl (meth)acrylate is preferably butyl acrylate, and more preferably n-butyl acrylate, because the effects of the present invention can be further exhibited.
[0053] The monomer component (m) preferably contains (meth)acrylic acid, and more preferably contains acrylic acid. The content of (meth)acrylic acid in the total amount of the monomer component (m) is preferably 1 wt% to 10 wt%, more preferably 1 wt% to 8 wt%, still more preferably 2 wt% to 7 wt%, particularly preferably 2 wt% to 6 wt%, and most preferably 2.5 wt% to 5.5 wt%. When the content of (meth)acrylic acid in the monomer component (m) is adjusted within the above range, a double-sided pressure-sensitive adhesive tape can be provided that can exhibit even more excellent impact resistance, even more excellent reprocessability, and even more excellent alcohol resistance.
[0054] The monomer component (m) may contain any other monomers. Such other monomers can be used alone or in combination.
[0055] The content of other monomers in the total amount of the monomer component (m) is preferably 0 wt% to 10 wt%, more preferably 0 wt% to 8 wt%, still more preferably 0 wt% to 6 wt%, particularly preferably 0 wt% to 4 wt%, and most preferably 0 wt% to 2 wt%. When the content of other monomers in the monomer component (m) is adjusted within the above range, a double-sided pressure-sensitive adhesive tape can be provided that can exhibit even more excellent impact resistance, even more excellent reprocessability, and even more excellent alcohol resistance.
[0056] Examples of other monomers include acrylic monomers containing an alicyclic structure, alkyl (meth)acrylates other than butyl (meth)acrylate, hydroxyl-containing monomers, carboxyl-containing monomers other than (meth)acrylic acid, nitrogen-containing cyclic structure monomers, cyclic ether group-containing monomers, glycol acrylate monomers, styrene-based monomers, amide group-containing monomers, amino group-containing monomers, imide group-containing monomers, vinyl ether monomers, silane-based monomers, and multifunctional monomers.
[0057] The acrylic monomer containing an alicyclic structure is preferably an acrylic monomer having a cyclic aliphatic hydrocarbon structure. The number of carbon atoms in the cyclic aliphatic hydrocarbon structure is preferably 3 or more, more preferably 6 to 24, still more preferably 6 to 18, and particularly preferably 6 to 12. Specific examples of such acrylic monomers containing an alicyclic structure include cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentyl (meth)acrylate.
[0058] Herein, the alkyl (meth)acrylate other than butyl (meth)acrylate does not include an alkyl (meth)acrylate having an alicyclic structure. Specific examples of the alkyl (meth)acrylate other than butyl (meth)acrylate include: alkyl (meth)acrylates each having a linear alkyl group (except n-butyl) at its ester end, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, n-pentadecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-heptadecyl (meth)acrylate, and n-octadecyl (meth)acrylate; and alkyl (meth)acrylate each having a linear alkyl group (except n-butyl) at its ester end, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptadecyl (meth)acrylate, and n-octadecyl (meth)acrylate; Alkyl (meth)acrylates having a branched alkyl group having 4 to 18 carbon atoms (excluding isobutyl), for example, isopropyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, tert-amyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, 2-propylheptyl (meth)acrylate, isoundecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isomyristyl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate and isostearyl (meth)acrylate.
[0059] Specific examples of hydroxyl-containing monomers include: hydroxyalkyl (meth)acrylates, such as 2-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; hydroxyalkylcycloalkyl (meth)acrylates, such as (4-hydroxymethylcyclohexyl)methyl (meth)acrylate; and other hydroxyl-containing monomers, such as hydroxyethyl (meth)acrylamide, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether. Among those hydroxyl-containing monomers, hydroxyalkyl (meth)acrylates are preferred because more excellent impact resistance can be exhibited, and hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 2 to 6 carbon atoms are more preferred, and 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate is even more preferred.
[0060] Specific examples of the carboxyl group-containing monomer other than (meth)acrylic acid include carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0061] Specific examples of monomers with nitrogen-containing cyclic structures include: lactam-based vinyl monomers, such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam and methylvinylpyrrolidone; vinyl-based monomers each having a nitrogen-containing heterocyclic ring, such as vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole and vinylmorpholine; and (meth)acrylic monomers each containing a heterocyclic ring such as a morpholine ring, a piperidine ring, a pyrrolidine ring or a piperazine ring (e.g., N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine and N-acryloylpyrrolidine).
[0062] Specific examples of the cyclic ether group-containing monomer include: epoxy group-containing monomers such as glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, methyl glycidyl (meth)acrylate and allyl glycidyl ether; oxetane group-containing monomers such as 3-oxetane methyl (meth)acrylate, 3-methyl-oxetane methyl (meth)acrylate, 3-ethyl-oxetane methyl (meth)acrylate, 3-butyl-oxetane methyl (meth)acrylate and 3-hexyl-oxetane methyl (meth)acrylate.
[0063] Specific examples of the diol-based acrylate monomer include polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.
[0064] Specific examples of the styrene-based monomers include styrene and α-methylstyrene.
[0065] Specific examples of the amide group-containing monomer include acrylamide, methacrylamide, diethylacrylamide, N-vinylpyrrolidone, N,N-dimethylacrylamide, N,N-(dimethyl)methacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N′-methylenebisacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, diacetoneacrylamide and N,N-hydroxyethylacrylamide.
[0066] Specific examples of the amino group-containing monomer include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate.
[0067] Specific examples of the monomer containing an imide group include cyclohexyl maleimide, isopropyl maleimide, N-cyclohexyl maleimide, and itaconic imide.
[0068] Specific examples of the silane-based monomer include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-acryloxydecyltriethoxysilane.
[0069] Specific examples of the polyfunctional monomer include: ester compounds of polyhydric alcohols and (meth)acrylic acid, such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate; vinyl (meth)acrylate; divinylbenzene; epoxy acrylate; polyester acrylate; polyurethane acrylate; dibutyl (meth)acrylate; and dihexyl (meth)acrylate.
[0070] <A-1-1-2. Polymer Component (P)>
[0071] The polymer component (P) is obtained by polymerizing the monomer component (m). The polymer component (P) is typically an acrylic polymer. The polymer component (P) can be used alone or in combination.
[0072] To the extent that the effects of the present invention are not impaired, any suitable production method can be used as the production method of the polymer component (P). Examples of such production methods include various types of radical polymerization, including: solution polymerization; active energy ray polymerization, such as UV polymerization; bulk polymerization; and emulsion polymerization. To the extent that the effects of the present invention are not impaired, any suitable polymerization conditions can be used as the polymerization conditions.
[0073] To the extent that the effects of the present invention are not impaired, any suitable polymerization structure can be used as the polymerization structure of the polymer component (P) to be obtained. Examples of such polymerization structures include random copolymers, block copolymers, and graft copolymers.
[0074] Any appropriate additive may be used as the additive to be used in the radical polymerization, such as a polymerization initiator, a chain transfer agent, or an emulsifier, to such an extent that the effects of the present invention are not impaired.
[0075] The polymerization solvent which can be used in solution polymerization etc. is, for example, ethyl acetate or toluene. The polymerization solvent can be used alone or in combination thereof.
[0076] Typically, solution polymerization is carried out under reaction conditions of a temperature of about 50° C. to about 70° C. and a time of about 5 hours to about 30 hours, after adding a polymerization initiator, in a stream of an inert gas such as nitrogen.
[0077] Any appropriate thermal polymerization initiator may be used as the polymerization initiator that can be used in solution polymerization, etc., to such an extent that the effects of the present invention are not impaired. The polymerization initiator may be used alone or in combination thereof. Examples of such polymerization initiators include azo-based initiators such as 2,2′-azobisisobutyronitrile, 2,2′-azobis-2-methylbutyronitrile, 2,2′-azobis(2-methylpropionic acid) dimethyl ester, 4,4′-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2′-azobis(2-amidinopropane) dihydrochloride, 2,2′-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2′-azobis(2-methylpropionamidine) disulfate, 2,2′-azobis(N,N′-dimethyleneisobutyramidine) and 2,2′-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); peroxide-based initiators, including persulfates such as potassium persulfate and ammonium persulfate, di(2-ethylhexyl) peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, dibenzoyl peroxide, tert-butyl peroxyisobutyrate, 1,1-di(tert-hexylperoxy)cyclohexane, tert-butyl hydroperoxide and hydrogen peroxide; and redox-based initiators each obtained by combining a peroxide and a reducing agent, such as a combination of a persulfate and sodium bisulfite, and a combination of a peroxide and sodium ascorbate.
[0078] The amount of the polymerization initiator used is preferably 1 part by weight or less, more preferably 0.005 to 1 part by weight, still more preferably 0.01 to 0.7 parts by weight, and particularly preferably 0.02 to 0.5 parts by weight, relative to 100 parts by weight of the total amount of the monomer component (m), for example, because the polymerization reaction can be effectively promoted.
[0079] Any suitable chain transfer agent may be used as the chain transfer agent to the extent that the effect of the present invention is not impaired. The chain transfer agent may be used alone or in combination. Examples of such chain transfer agents include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol.
[0080] The chain transfer agent is preferably used in an amount of 0.1 parts by weight or less relative to 100 parts by weight of the total amount of the monomer component (m) because, for example, the polymerization reaction can be efficiently advanced.
[0081] Any appropriate emulsifier may be used as the emulsifier to the extent that the effect of the present invention is not impaired. The emulsifier may be used alone or in combination. Examples of such emulsifiers include anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, ammonium polyoxyethylene alkyl ether sulfate, and sodium polyoxyethylene alkylphenyl ether sulfate; and nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene fatty acid esters, and polyoxyethylene-polyoxypropylene block polymers.
[0082] From the viewpoint of polymerization stability and mechanical stability, the amount of the emulsifier used is preferably 5 parts by weight or less, more preferably 0.3 to 5 parts by weight, still more preferably 0.4 to 3 parts by weight, particularly preferably 0.5 to 1 part by weight, relative to 100 parts by weight of the total amount of the monomer component (m).
[0083] When UV polymerization is performed, it is preferred to use a photopolymerization initiator.
[0084] Any suitable photopolymerization initiator may be used as the photopolymerization initiator to the extent that the effect of the present invention is not impaired. The photopolymerization initiator may be used alone or in combination. Examples of such photopolymerization initiators include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, and acylphosphine oxide photopolymerization initiators.
[0085] Specific examples of the benzoin ether-based photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one (for example, a commercially available product under the trade name "Irgacure 651" from BASF), and anisole methyl ether.
[0086] Specific examples of the acetophenone-based photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone (e.g., a commercial product available under the trade name "Irgacure 184" from BASF), 4-phenoxydichloroacetophenone, 4-tert-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (e.g., a commercial product available under the trade name "Irgacure 2959" from BASF), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (e.g., a commercial product available under the trade name "DAROCUR 1173" from BASF), and methoxyacetophenone.
[0087] Specific examples of the α-ketol-based photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)-phenyl]-2-hydroxy-2-methylpropane-1-one.
[0088] A specific example of the aromatic sulfonyl chloride-based photopolymerization initiator is 2-naphthalenesulfonyl chloride.
[0089] A specific example of the photoactive oxime-based photopolymerization initiator is 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime.
[0090] A specific example of the benzoin-based photopolymerization initiator is benzoin.
[0091] A specific example of the benzil-based photopolymerization initiator is benzil.
[0092] Specific examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenylketone.
[0093] A specific example of the ketal-based photopolymerization initiator is benzyl dimethyl ketal.
[0094] Specific examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0095] Specific examples of the acylphosphine oxide-based photopolymerization initiator include bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)(2,4,4-trimethylpentyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-n-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)-(2-methylpropane-1-yl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-(1-methylpropane-1-yl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-tert-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)cyclohexylphosphine oxide, bis(2,6-dimethoxybenzoyl)octylphosphine oxide, bis(2-methoxybenzoyl)(2-methylpropane-1-yl)phosphine oxide, -1-yl) phosphine oxide, bis(2-methoxybenzoyl)(1-methylpropane-1-yl) phosphine oxide, bis(2,6-diethoxybenzoyl)(2-methylpropane-1-yl) phosphine oxide, bis(2,6-diethoxybenzoyl)(1-methylpropane-1-yl) phosphine oxide, bis(2,6-dibutoxybenzoyl)(2-methylpropane-1-yl) phosphine oxide, bis(2,4-dimethoxybenzoyl)(2-methylpropane-1-yl) phosphine oxide, bis(2,4,6-trimethylbenzoyl)(2,4-dipentyloxyphenyl) phosphine oxide, bis(2,6-dimethoxybenzoyl)benzyl phosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropyl phosphine oxide, bis(2,6 bis(2,6-dimethoxybenzoyl)-2-phenylethylphosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylethylphosphine oxide, 2,6-dimethoxybenzoylbenzylbutylphosphine oxide, 2,6-dimethoxybenzoylbenzyloctylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,5-diisopropylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2-methylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-4-methylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,5-diethylphenylphosphine oxide phosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,3,5,6-tetramethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)isobutylphosphine oxide, 2,6-dimethoxybenzoyl-2,4,6-trimethylbenzoyl-n-butylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-butoxyphenylphosphine oxide, 1,10-bis[bis(2,4,6-trimethylbenzoyl)phosphine oxide] decane, and tri(2-methylbenzoyl)phosphine oxide.
[0096] From the viewpoint of, for example, the expression of satisfactory polymerizability, the amount of the photopolymerization initiator used is preferably 5 parts by weight or less, more preferably 0.01 to 5 parts by weight, still more preferably 0.05 to 3 parts by weight, particularly preferably 0.05 to 1.5 parts by weight, most preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the total amount of the monomer component (m).
[0097] When UV polymerization is performed, polyfunctional (meth)acrylates are preferably used.
[0098] Any appropriate polyfunctional (meth)acrylate may be used as the polyfunctional (meth)acrylate to such an extent that the effects of the present invention are not impaired. The polyfunctional (meth)acrylate may be used alone or in combination. Specific examples of such multifunctional (meth)acrylates include: ester compounds of polyols and (meth)acrylic acid, such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate; vinyl (meth)acrylate; divinylbenzene; epoxy acrylate; polyester acrylate; polyurethane acrylate; butyl di(meth)acrylate; and hexyl di(meth)acrylate.
[0099] From the viewpoint of, for example, the expression of satisfactory crosslinking properties, the amount of the multifunctional (meth)acrylate used is preferably 5 parts by weight or less, more preferably 0.01 to 5 parts by weight, still more preferably 0.05 to 3 parts by weight, particularly preferably 0.05 to 1.5 parts by weight, most preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the total amount of the monomer component (m).
[0100] Any appropriate UV polymerization method can be used as a method for UV polymerization to the extent that the effects of the present invention are not impaired. Such a UV polymerization method is, for example, as follows: the monomer component (m) is blended with a photopolymerization initiator and, if necessary, a multifunctional (meth)acrylate, and the resultant is irradiated with UV light.
[0101] The weight-average molecular weight of the polymer component (P) is preferably from 100,000 to 3,000,000, more preferably from 300,000 to 2,000,000, still more preferably from 500,000 to 1,500,000, and particularly preferably from 500,000 to 1,000,000, because the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention can exhibit more excellent impact resistance. The weight-average molecular weight is a value measured by gel permeation chromatography (GPC) and converted to polystyrene. It may be difficult to measure the weight-average molecular weight of the polymer component (P) obtained by living energy ray polymerization.
[0102] <A-1-1-3. Tackifying resin>
[0103] The pressure-sensitive adhesive composition may contain a tackifying resin. The tackifying resin can be used alone or in combination thereof.
[0104] To the extent that the effects of the present invention are not impaired, any suitable tackifying resin can be used as the tackifying resin. Examples of such tackifying resins include phenolic tackifying resins, terpene tackifying resins, modified terpene tackifying resins, rosin tackifying resins, hydrocarbon tackifying resins, epoxy tackifying resins, polyamide tackifying resins, elastomeric tackifying resins, and ketone tackifying resins.
[0105] Examples of phenolic tackifying resins include terpene-phenol resins, hydrogenated terpene-phenol resins, alkylphenol resins, and rosin-phenol resins. A terpene-phenol resin refers to a polymer containing terpene residues and phenol residues, and is a concept including both a copolymer of terpenes and phenol compounds (terpene-phenol copolymer resin) and a phenol-modified product of a homopolymer or copolymer of terpenes (phenol-modified terpene resin). Examples of terpenes forming such a terpene-phenol resin include monoterpenes such as α-pinene, β-pinene, and limonene (including d-type, l-type, and d / l-type (dipentene)). A hydrogenated terpene-phenol resin refers to a hydrogenated terpene-phenol resin having a structure obtained by hydrogenating such a terpene-phenol resin, and is sometimes referred to as a hydrogenated terpene-phenol resin. An alkylphenol resin is a resin obtained from an alkylphenol and formaldehyde (oil-soluble phenolic resin). Examples of alkylphenol resins include novolak-type resins and resole-type resins. Examples of rosin-phenol resins include phenol-modified products of rosins or various rosin derivatives (including rosin esters, unsaturated fatty acid-modified rosins, and unsaturated fatty acid-modified rosin esters). A rosin-phenol resin is, for example, a rosin-phenol resin obtained by the following method: the method involves adding phenol to a rosin or various rosin derivatives with an acid catalyst and thermally polymerizing the resulting product.
[0106] Examples of terpene-based tackifying resins include polymers of terpenes (typically monoterpenes) such as α-pinene, β-pinene, d-limonene, l-limonene and dipentene. A terpene homopolymer is, for example, an α-pinene polymer, a β-pinene polymer or a dipentene polymer.
[0107] Examples of the modified terpene resin include styrene-modified terpene resins and hydrogenated terpene resins.
[0108] The concept of rosin-based tackifying resins includes both rosins and rosin derivative resins. Examples of rosins include: unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; and modified rosins obtained by modifying these unmodified rosins by hydrogenation, disproportionation, or polymerization (e.g., hydrogenated rosin, disproportionated rosin, polymerized rosin, and any other chemically modified rosin).
[0109] Examples of rosin derivative resins include: rosin esters such as unmodified rosin esters as esters of unmodified rosin and alcohols, and modified rosin esters as esters of modified rosin and alcohols; unsaturated fatty acid-modified rosins obtained by modifying rosins with unsaturated fatty acids; unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids; rosin alcohols obtained by subjecting rosins or rosin derivative resins (e.g., rosin esters, unsaturated fatty acid-modified rosins, and unsaturated fatty acid-modified rosin esters) to reduction treatment; and metal salts thereof. Examples of rosin esters include methyl esters, triethylene glycol esters, glycerol esters, and pentaerythritol esters of unmodified rosins or modified rosins (e.g., hydrogenated rosin, disproportionated rosin, and polymerized rosin).
[0110] Examples of hydrocarbon-based tackifying resins include aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic-aromatic petroleum resins (e.g., styrene-olefin copolymers), aliphatic-alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone-based resins, and coumarone-indene-based resins.
[0111] In the case of Form 1, the content of the tackifier resin in the pressure-sensitive adhesive composition is preferably 1 to 50 parts by weight, more preferably 5 to 30 parts by weight, still more preferably 8 to 25 parts by weight, particularly preferably 10 to 20 parts by weight, relative to 100 parts by weight of the polymer component (P).
[0112] In the case of form 2, the content of the tackifier resin in the pressure-sensitive adhesive composition is preferably 1 to 50 parts by weight, more preferably 5 to 30 parts by weight, still more preferably 8 to 25 parts by weight, and particularly preferably 10 to 20 parts by weight, relative to 100 parts by weight of the total amount of the monomer component (m).
[0113] In the case of Form 3, the content of the tackifying resin in the pressure-sensitive adhesive composition is preferably 1 to 50 parts by weight, more preferably 5 to 30 parts by weight, still more preferably 8 to 25 parts by weight, and particularly preferably 10 to 20 parts by weight, based on 100 parts by weight of the total amount of the polymer component (P) and the monomer component (m).
[0114] <A-1-1-4. Crosslinking agent>
[0115] The pressure-sensitive adhesive composition may contain a crosslinking agent. The crosslinking agent can be used alone or in combination. When the pressure-sensitive adhesive composition contains a crosslinking agent, the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention can exhibit more excellent alcohol resistance.
[0116] To the extent that the effects of the present invention are not impaired, any suitable crosslinking agent can be used as the crosslinking agent. Examples of such crosslinking agents include isocyanate-based crosslinking agents and non-isocyanate-based crosslinking agents.
[0117] To the extent that the effects of the present invention are not impaired, any suitable isocyanate-based crosslinking agent can be used as the isocyanate-based crosslinking agent. Examples of such isocyanate-based crosslinking agents include aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates, as well as dimers and trimers of those diisocyanates. Specific examples thereof include toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, butane-1,4-diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, dicyclohexylmethane-4,4-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, and m-tetramethylxylylene diisocyanate, as well as their dimers and trimers, and polyphenylmethane polyisocyanate. In addition, the trimer can be, for example, an isocyanurate type, a biuret type, or a urethane type.
[0118] Commercially available products can be used as isocyanate-based crosslinking agents. Examples of commercially available products of polyisocyanates include products available under the trade name "TAKENATE 600" from Mitsui Chemicals, Inc., products available under the trade name "DURANATE TPA100" from Asahi Kasei Chemicals Corporation, and products available under the trade names "CORONATE L", "CORONATE HL", "CORONATE HK", "CORONATE HX" and "CORONATE 2096" from Nippon Polyurethane Industry Co., Ltd.
[0119] Examples of non-isocyanate crosslinking agents include epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, carbodiimide crosslinking agents, hydrazine crosslinking agents, amine crosslinking agents, peroxide crosslinking agents, metal chelate crosslinking agents, metal alkoxide crosslinking agents, metal salt crosslinking agents, and silane coupling agents.
[0120] In at least one exemplary embodiment of the present invention, an epoxy crosslinking agent can be used as a non-isocyanate crosslinking agent. The epoxy crosslinking agent is preferably a compound having two or more epoxy groups in its molecule, and more preferably an epoxy crosslinking agent having 3 to 5 epoxy groups in its molecule.
[0121] Specific examples of epoxy crosslinking agents include N, N, N', N'-tetraglycidyl-m-xylenediamine, 1,3-bis(N, N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, and polyglycerol polyglycidyl ether. Examples of commercially available epoxy crosslinking agents include products available under the trade names "TETRAD-C" and "TETRAD-X" from Mitsubishi Gas Chemical Company, products available under the trade name "EPICLON CR-5L" from DIC Corporation, products available under the trade name "DENACOL EX-512" from Nagase ChemteX Corporation, and products available under the trade name "TEPIC-G" from Nissan Chemical Industries, Ltd.
[0122] In the case of Form 1, the content of the crosslinking agent in the pressure-sensitive adhesive composition is preferably 0.01 part by weight to 10 parts by weight, more preferably 0.1 part by weight to 8 parts by weight, still more preferably 0.5 part by weight to 7 parts by weight, and particularly preferably 1.5 parts by weight to 5 parts by weight, based on 100 parts by weight of the polymer component (P). When the content of the crosslinking agent in the pressure-sensitive adhesive composition falls within the above range, a double-sided pressure-sensitive adhesive tape can be provided that can exhibit more excellent impact resistance, more excellent reprocessability, and more excellent alcohol resistance all together.
[0123] In the case of Form 2, the content of the crosslinking agent in the pressure-sensitive adhesive composition is preferably 0.01 part by weight to 10 parts by weight, more preferably 0.1 part by weight to 8 parts by weight, still more preferably 0.5 part by weight to 7 parts by weight, and particularly preferably 1.5 parts by weight to 3 parts by weight, based on the total amount of 100 parts by weight of the monomer component (m). When the content of the crosslinking agent in the pressure-sensitive adhesive composition falls within the above range, a double-sided pressure-sensitive adhesive tape can be provided that can exhibit more excellent impact resistance, more excellent reprocessability, and more excellent alcohol resistance all together.
[0124] In the case of Form 3, the content of the crosslinking agent in the pressure-sensitive adhesive composition is preferably 0.01 part by weight to 10 parts by weight, more preferably 0.1 part by weight to 8 parts by weight, still more preferably 0.5 part by weight to 7 parts by weight, and particularly preferably 1.5 parts by weight to 3 parts by weight, based on 100 parts by weight of the total amount of the polymer component (P) and the monomer component (m). When the content of the crosslinking agent in the pressure-sensitive adhesive composition falls within the above range, a double-sided pressure-sensitive adhesive tape can be provided that can exhibit more excellent impact resistance, more excellent reprocessability, and more excellent alcohol resistance all together.
[0125] In the pressure-sensitive adhesive composition, an isocyanate-based crosslinking agent and a non-isocyanate-based crosslinking agent (for example, an epoxy-based crosslinking agent) can be used in combination. In this case, the ratio of the content of the non-isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition to the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition is preferably 1 / 50 or less, more preferably 1 / 75 or less, still more preferably 1 / 100 or less, and particularly preferably 1 / 150 or less, because the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention can exhibit more excellent oil resistance. In addition, the ratio of the content of the non-isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition to the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition is preferably 1 / 1,000 or more, more preferably 1 / 500 or more, because the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention can exhibit more excellent oil resistance.
[0126] <A-2. Substrate layer>
[0127] The substrate layer may be a single layer, or may include two or more layers. In the case of two or more layers, all of the substrate layers may have the same composition, or at least one of the substrate layers may be different in composition from the others.
[0128] The thickness of the substrate layer is preferably 5 μm to 50 μm because the effect of the present invention can be further expressed, and is more preferably 5 μm to 30 μm, still more preferably 10 μm to 30 μm.
[0129] The base material layer is preferably formed of a resin film containing a resin material as a main component.
[0130] As used herein, the term "main component" means the component blended in the highest proportion, typically the component contained at more than 50 wt%.
[0131] The content of resin material in the resin film is preferably greater than 50wt% and less than 100wt%, more preferably 60wt% to 100wt%, even more preferably 70wt% to 100wt%, even more preferably 80wt% to 100wt%, particularly preferably 90wt% to 100wt%, most preferably 95wt% to 100wt%.
[0132] As used herein, the term "resin film" typically means a substantially non-foamed resin film. That is, herein, the resin film may be substantially free of the bubbles (no voids) present inside the resin film. Therefore, herein, the concept of "resin film" is distinguished from the so-called foam film. In addition, herein, the resin film is typically a substantially non-porous film, which is a concept distinguished from the so-called non-woven fabric or woven fabric. Herein, the following can be preferably used as resin film: a substrate that does not contain a porous layer such as a foam, non-woven fabric or woven fabric, i.e. a substrate formed by a non-porous layer. Compared with a foam, non-woven fabric or woven fabric, a resin film is generally inclined to be excellent in mechanical strengths such as tensile strength.
[0133] Examples of resin materials for forming the resin film include polyolefin resins (e.g., polyethylene, polypropylene, ethylene-propylene copolymers, or ethylene-vinyl acetate copolymers), polyvinyl chloride resins (typically soft polyvinyl chloride resins), polyvinyl acetate resins, polyurethane resins (e.g., ether polyurethane, ester polyurethane, or carbonate polyurethane), polyurethane (meth) acrylate resins, thermoplastic elastomers (e.g., olefin elastomers, styrene elastomers, or acrylic elastomers), polyester resins (e.g., polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, or polybutylene naphthalate), polycarbonate resins, polyamide resins, polyimide resins, fluororesins, and cellulose resins such as cellophane resins. These resin materials can be used alone or in combination. A preferred example of the resin material for forming the resin film is at least one selected from the group consisting of polyolefin resins, polyvinyl chloride resins, polyurethane resins and polyester resins, a more preferred example is a polyolefin resin or a polyurethane resin, and a more preferred example is a polyurethane resin. That is, a preferred example of the resin film is at least one selected from the group consisting of polyolefin resin film, polyvinyl chloride resin film, polyurethane resin film and polyester resin film, a more preferred example is a polyolefin resin film or a polyurethane resin film, and a more preferred example is a polyurethane resin film. When the resin film is the above-mentioned resin film, a pressure-sensitive adhesive tape that can show both more excellent impact resistance and more excellent reprocessability can be provided.
[0134] In at least one exemplary embodiment of the present invention, the substrate layer is a polyurethane resin film containing a polyurethane resin as a main component. The polyurethane resin film is typically formed of a material that does not substantially show a yield point. The polyurethane resin film can achieve satisfactory physical properties even without adding, for example, additive components such as plasticizers, and can therefore be used as a substrate layer that is preferred in the technology disclosed herein because such additive components are prevented from seeping out.
[0135] Specifically, the content of the polyurethane resin in the polyurethane resin film as a whole is preferably 50wt% to 100wt%, more preferably 70wt% to 100wt%, still more preferably 90wt% to 100wt%, particularly preferably 95wt% to 100wt%, and most preferably substantially 100wt%. When the resin film as a whole contains the polyurethane resin as a main component, the effect of the present invention can be further exhibited.
[0136] Herein, the case described as “substantially 100 wt %” means that trace amounts of impurities and the like may be contained to such an extent that the effects of the present invention are not impaired, and such a case may generally be described as “100 wt %”.
[0137] The polyurethane resin film may be a film formed of a polymer blend of a polyurethane resin and other resins. The other resin is preferably at least one selected from the group consisting of, for example, acrylic resins, polyolefin resins, polyester resins, and polycarbonate resins.
[0138] Polyurethane resin is a polymer compound synthesized by polyaddition reaction of polyol (e.g., diol) and polyisocyanate (e.g., diisocyanate) in a predetermined ratio. The NCO / OH ratio of polyurethane only needs to be appropriately set based on the conventional technical knowledge known to those of ordinary skill in the art in order to achieve the desired mechanical properties (e.g., breaking strength, breaking elongation, and tensile resilience).
[0139] Examples of polyols that can be used to synthesize polyurethane resins include: diols, such as ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,8-octanediol, polyoxytetramethylene glycol, diethylene glycol, polyethylene glycol, or polypropylene glycol; polyester polyols, which are polycondensates of diols and dicarboxylic acids (e.g., adipic acid, azelaic acid, or sebacic acid); and carbonate diols, such as polyalkylene carbonate diols. These polyols can be used alone or in combination.
[0140] Examples of polyisocyanates that can be used for synthesizing the polyurethane-based resin include aromatic, aliphatic, and alicyclic diisocyanates, and polymers (eg, dimers and trimers) of diisocyanates. The example of diisocyanate comprises toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, butane-1,4-diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, dicyclohexylmethane-4,4-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate and meta-tetramethylxylylene diisocyanate.These diisocyanates can be used alone or in combination.Among diisocyanates, aromatic diisocyanates are preferred, because the effect of the present invention can be further shown.
[0141] In addition to polyols and polyisocyanates, other copolymer components can also be introduced into the polyurethane resin. Examples of other copolymer components include monocarboxylic acids, dicarboxylic acids, trifunctional or higher polycarboxylic acids, hydroxycarboxylic acids, alkoxycarboxylic acids and derivatives thereof. Other copolymer components can be used alone or in combination.
[0142] It is appropriate to set the proportion of other copolymer components in the polyurethane-based resin to approximately less than 30 wt % (eg, less than 10 wt %, typically less than 5 wt %).
[0143] In the case where a polyurethane-based resin is used as the resin material for forming the resin film, the polyurethane-based resin preferably contains thermoplastic polyurethane because the effect of the present invention can be sufficiently exhibited. The number of kinds of the thermoplastic polyurethane may be only one, or two or more.
[0144] In the above case, the content of thermoplastic polyurethane in the polyurethane resin is preferably 50wt% to 100wt%, more preferably 70wt% to 100wt%, still more preferably 90wt% to 100wt%, particularly preferably 95wt% to 100wt%, and most preferably substantially 100wt%. When the resin film as a whole contains thermoplastic polyurethane as a main component, the effect of the present invention can be further exhibited.
[0145] Any appropriate thermoplastic polyurethane may be used as the thermoplastic polyurethane to the extent that the effect of the present invention is not impaired. Examples of such thermoplastic polyurethanes (commonly referred to as TPU) are block copolymers comprising hard segments and soft segments. Preferred examples of such thermoplastic polyurethanes are at least one selected from the group consisting of polyester TPU, polyether TPU, and polycarbonate TPU, because the effect of the present invention can be more fully exhibited.
[0146] A commercially available product can be used as the thermoplastic polyurethane.
[0147] The substrate layer can include any appropriate additive as required. The example of the additive that can be included in the substrate layer includes a release agent, a UV absorber, a heat stabilizer, a filler, a lubricant, a colorant (for example, a dye), an antioxidant, an anti-build up agent, an anti-blocking agent, a foaming agent, and polyethylene imine. These additives can be used alone or in combination. The content of the additive in the substrate layer is preferably below 10wt%, more preferably below 7wt%, still more preferably below 5wt%, particularly preferably below 2wt%, most preferably below 1wt%.
[0148] 《B. Method for producing double-sided pressure-sensitive adhesive tape》
[0149] The double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention can be manufactured by any appropriate method to the extent that the effects of the present invention are not impaired. The following method is given as an example of such a method: a pressure-sensitive adhesive layer is prepared separately and attached to a substrate layer by any appropriate method. When the double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention is as follows Figure 1When the case where the pressure-sensitive adhesive layer is included on both sides of the substrate layer is taken as an example, one example of the method is a method involving laminating two pressure-sensitive adhesive layers to the two surfaces of the substrate layer, respectively. For example, a laminator can be used for lamination. In addition, after lamination, aging can be performed at any appropriate temperature for any appropriate time as needed.
[0150] Example
[0151] Now, the present invention is specifically described by examples. However, the present invention is by no means limited to examples. The test and evaluation methods in the examples, etc. are as follows. Unless otherwise specified, the term "part" in the following description means "part by weight", and unless otherwise specified, the term "%" in the following description means "wt%".
[0152] <Weight Average Molecular Weight>
[0153] The weight average molecular weight is determined from a value converted into standard polystyrene obtained by gel permeation chromatography (GPC). An apparatus available under the model "HLC-8320GPC" (column: TSKgel GMH-H(S), manufactured by Tosoh Corporation) is used as a GPC apparatus.
[0154] <Force at 100% strain>
[0155] The double-sided pressure-sensitive adhesive sheet is punched with a dumbbell-shaped punching blade (manufactured by Kobunshi Keiki Co., Ltd., trade name: No.3 dumbbell-shaped die head), and its release liner is removed. Thus, a measurement sample is manufactured. The measurement sample is placed in a tensile tester ("PRECISION UNIVERSAL TESTER AUTOGRAPH AG-IS 50N", manufactured by Shimadzu Corporation) so that the two ends of the measurement sample are symmetrical and the length in the tensile direction of the double-sided tape punched into a dumbbell shape is 20mm. Afterwards, the measurement sample is pulled at a speed of 50mm / min, and the stress (N) of the measurement sample at 100% elongation is recorded. Next, the force under 100% strain is calculated by the following equation.
[0156] (Force at 100% strain) = (Stress at 100% elongation) / (Width of measured sample)
[0157] <Impact Resistance>
[0158] The double-sided pressure-sensitive adhesive tape sandwiched between the release liners was punched into a frame shape of 2mm in width and 24.5 mm square in shape to provide an evaluation sample. The evaluation sample was set between a square stainless steel plate (the plate had a hole of 20mm long × 20mm wide in its central portion) with a thickness of 2mm and a shape of 50mm × 50mm and a square stainless steel plate (25mm square in shape and 3mm in thickness), and was pressed onto the plate (62N × 10 seconds) in such a way that the force was uniformly applied to the sample in the direction of gravity. Afterwards, the resultant was left to stand at 80°C for 30 minutes and taken out. Afterwards, the resultant was returned to an environment of 23°C to provide a test piece. A cylindrical measuring table with a length of 50mm, an outer diameter of 49mm and an inner diameter of 43mm was set on the base of a Du Pont type impact tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.), and the test piece was mounted thereon in such a way that the square stainless steel plate was located on the lower side. A stainless steel impact shaft with a tip radius of 3.1 mm is mounted on the test piece, and the weight of the drop weight and its drop height are changed as follows to increase the energy until the stripping of the tape occurs: when the weight is 100 g, the height is changed from 50 mm to 500 mm in increments of 50 mm; when the weight is 150 g, the height is changed from 350 mm to 500 mm in increments of 50 mm; when the weight is 200 g, the height is changed from 400 mm to 500 mm in increments of 50 mm; and when the weight is 300 g, the height is changed from 350 mm to 500 mm in increments of 50 mm. At this time, for the energy that has been evaluated, no test is performed, and the load and height are set in such a way that the amount of energy does not overlap each other. Afterwards, the energy immediately before stripping is calculated by the expression "load × height" and used as the result. In actual use, the energy until stripping is required to be 0.3 J or more.
[0159] <Alcohol resistance measurement>
[0160] A PET film (without release treatment) having a thickness of 50 μm was attached to one pressure-sensitive adhesive layer surface of the double-sided pressure-sensitive adhesive tape obtained in each of Examples and Comparative Examples to back the surface. The backed pressure-sensitive adhesive tape was cut into a size of 10 mm wide × 100 mm long to produce a sample sheet.
[0161] By passing through once with a 2kg roller, the surface of the pressure-sensitive adhesive layer of the obtained test piece is pressed to a stainless steel plate (SUS304BA plate) (manufactured by Nippon Kinzoku Co., Ltd.) washed with toluene, thereby manufacturing a measurement sample. The measurement sample is left to stand for 30 minutes under the environment of 23°C and 50%RH, and then its peel strength (N / 10mm) is measured under the conditions of a tensile tester (manufactured by Shimadzu Corporation, "PRECISION UNIVERSAL TESTER, AUTOGRAPH AG-IS 50N") in accordance with JIS Z0237:2000 at a tensile speed of 300mm / min and a peeling angle of 180°. This value is defined as the pressure-sensitive adhesive strength A0 (N / 10mm) before immersion. At the same time, the measurement sample manufactured in the same manner as above is left to stand for 30 minutes under the environment of 23°C and 50%RH. Afterwards, the measurement sample is immersed in an isopropanol bath and kept for 24 hours under the environment of 40°C and 90%RH. Afterwards, the measurement sample is pulled out from the isopropanol bath, and the isopropanol solution adhering to its periphery is gently wiped off. The measurement sample is left to stand for 30 minutes under an environment of 23°C and 50%RH, and then its peel strength A1 (N / 10mm) is measured in the same manner as the pressure-sensitive adhesive strength before immersion. This value is defined as the pressure-sensitive adhesive strength after immersion. The pressure-sensitive adhesive strength maintenance rate is calculated by using the following equation and the measured value thus obtained: pressure-sensitive adhesive strength maintenance rate (%) = (pressure-sensitive adhesive strength A1 after immersion / pressure-sensitive adhesive strength A0 before immersion) × 100; and alcohol resistance is evaluated by the following grade evaluation. In actual use, the pressure-sensitive adhesive strength maintenance rate is required to be 75% or more.
[0162] Grade 1: The pressure-sensitive adhesive strength maintenance rate is less than 50%.
[0163] Rank 2: The pressure-sensitive adhesive strength maintenance rate is 50% or more and less than 75%.
[0164] Rank 3: The pressure-sensitive adhesive strength maintenance rate is 75% or more and less than 85%.
[0165] Rank 4: The pressure-sensitive adhesive strength maintenance rate is 85% or more and less than 95%.
[0166] Level 5: The pressure-sensitive adhesive strength maintenance rate is 95% or more.
[0167] <Reprocessability>
[0168] The double-sided pressure-sensitive adhesive tape obtained in each of Examples and Comparative Examples sandwiched between release liners on both sides was cut into a size of 10 mm wide×50 mm long, thereby producing a test piece.
[0169] One release liner of the test piece was peeled off, and the pressure-sensitive adhesive layer surface of the test piece was crimped to a stainless steel plate (SUS304BA plate) washed with toluene (manufactured by Nippon Kinzoku Co., Ltd.) by passing through it back and forth once with a 2kg roller. The resulting product was stored for 24 hours under heating at 50°C. Afterwards, the other release liner was peeled off, and the short side end of the test piece was peeled off from the stainless steel plate, and the pull was continued at an angle of 30° relative to the adherend to determine the reprocessability. The reprocessability was evaluated by the following criteria. In actual use, the reprocessability corresponding to more than 3 in the following criteria was required.
[0170] Grade 1: The tape tears and cannot be peeled off.
[0171] Grade 2: The tape peels away but does not tear when pulled at a speed of less than 0.5 m / min.
[0172] Grade 3: The tape peels away but is not torn when pulled at a speed of 0.5 m / min or more and less than 1.0 m / min.
[0173] Grade 4: The tape peels away but is not torn when pulled at a speed of 1.0 m / min or more and less than 5.0 m / min.
[0174] Grade 5: The tape peels off even when pulled at a speed of more than 5.0 m / min.
[0175] [Manufacturing Example 1]: Manufacture of pressure-sensitive adhesive layer (1)
[0176] 95 parts of butyl acrylate (BA) and 5 parts of acrylic acid (AA) as monomer components and 233 parts of ethyl acetate as a polymerization solvent were charged into a reaction vessel including a stirrer, a thermometer, a nitrogen introduction tube, a reflux condenser, and a dropping funnel, and stirred for 2 hours while introducing nitrogen into the vessel. After oxygen in the polymerization system had been removed as described above, 0.2 parts of 2,2′-azobisisobutyronitrile was added to the mixture as a polymerization initiator, and the whole was subjected to solution polymerization at 60° C. for 8 hours, thereby providing a solution of an acrylic polymer. The weight average molecular weight of the acrylic polymer was 700,000.
[0177] With respect to 100 parts of the acrylic polymer in the obtained acrylic polymer solution, 20 parts of a terpene-phenol resin (trade name: "YS POLYSTER T-115", softening point: about 115° C., hydroxyl value: 30 mgKOH / g to 60 mgKOH / g, manufactured by Yasuhara Chemical Co., Ltd.) as a tackifier resin, 3 parts of an isocyanate crosslinking agent (trade name: "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.02 parts of an epoxy crosslinking agent (trade name: "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Company, Inc.) as a crosslinking agent, and 6 parts of a product available under the trade name "AT-DN101 BLACK" (manufactured by Dainichiseika Color & Chemicals) as a black pigment were added. Mfg. Co., Ltd.) was added to the solution, and the contents were stirred and mixed to prepare a pressure-sensitive adhesive composition (1).
[0178] The pressure-sensitive adhesive composition (1) was applied to the release surface of a 38 μm thick polyester release liner (trade name: "DIAFOILMRF", manufactured by Mitsubishi Polyester Film, Inc.) and dried at 100° C. for 2 minutes to form a 97.5 μm thick pressure-sensitive adhesive layer (1).
[0179] [Manufacturing Example 2]: Manufacture of pressure-sensitive adhesive layer (2)
[0180] A pressure-sensitive adhesive layer (2) having a thickness of 92.5 μm was formed in the same manner as in Production Example 1, except that: the amount of the isocyanate crosslinking agent (trade name: "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) used was changed to 5 parts; and the thickness of the final pressure-sensitive adhesive layer was set to 92.5 μm.
[0181] [Manufacturing Example 3]: Manufacture of pressure-sensitive adhesive layer (3)
[0182] A pressure-sensitive adhesive layer (3) having a thickness of 87.5 μm was formed in the same manner as in Production Example 1, except that: the amount of the isocyanate crosslinking agent (trade name: "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) used was changed to 5 parts; and the thickness of the final pressure-sensitive adhesive layer was set to 87.5 μm.
[0183] [Manufacturing Example 4]: Manufacture of pressure-sensitive adhesive layer (4)
[0184] A pressure-sensitive adhesive layer (4) having a thickness of 80.0 μm was formed in the same manner as in Production Example 1 except that the thickness of the final pressure-sensitive adhesive layer was set to 80.0 μm.
[0185] [Manufacturing Example 5]: Manufacture of pressure-sensitive adhesive layer (5)
[0186] A pressure-sensitive adhesive layer (5) having a thickness of 85.0 μm was formed in the same manner as in Production Example 1 except that the thickness of the final pressure-sensitive adhesive layer was set to 85.0 μm.
[0187] [Manufacturing Example 6]: Manufacture of pressure-sensitive adhesive layer (6)
[0188] 93 parts of butyl acrylate (BA) and 7 parts of acrylic acid (AA) as monomer components and 233 parts of ethyl acetate as a polymerization solvent were charged into a reaction vessel including a stirrer, a thermometer, a nitrogen introduction tube, a reflux condenser, and a dropping funnel, and stirred for 2 hours while introducing nitrogen into the vessel. After oxygen in the polymerization system had been removed as described above, 0.2 parts of 2,2′-azobisisobutyronitrile was added to the mixture as a polymerization initiator, and the whole was subjected to solution polymerization at 60° C. for 8 hours, thereby providing a solution of an acrylic polymer. The weight average molecular weight of the acrylic polymer was 1,400,000.
[0189] With respect to 100 parts of the acrylic polymer in the obtained acrylic polymer solution, 20 parts of a terpene-phenol resin (trade name: "YS POLYSTER T-115", softening point: about 115° C., hydroxyl value: 30 mgKOH / g to 60 mgKOH / g, manufactured by Yasuhara Chemical Co., Ltd.) as a tackifier resin, 3 parts of an isocyanate crosslinking agent (trade name: "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.02 parts of an epoxy crosslinking agent (trade name: "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Company, Inc.) as a crosslinking agent, and 6 parts of a product available under the trade name "AT-DN101 BLACK" (manufactured by Dainichiseika Color & Chemicals) as a black pigment were added. Mfg. Co., Ltd.) was added to the solution, and the contents were stirred and mixed to prepare a pressure-sensitive adhesive composition (6).
[0190] The pressure-sensitive adhesive composition (6) was applied to the release surface of a 38 μm thick polyester release liner (trade name: "DIAFOILMRF", manufactured by Mitsubishi Polyester Film, Inc.) and dried at 100°C for 2 minutes to form a pressure-sensitive adhesive layer (6) having a thickness of 87.5 μm.
[0191] [Manufacturing Example 7]: Manufacture of pressure-sensitive adhesive layer (7)
[0192] 97 parts of butyl acrylate (BA) and 3 parts of acrylic acid (AA) as monomer components and 233 parts of ethyl acetate as a polymerization solvent were charged into a reaction vessel including a stirrer, a thermometer, a nitrogen introduction tube, a reflux condenser, and a dropping funnel, and stirred for 2 hours while introducing nitrogen into the vessel. After oxygen in the polymerization system had been removed as described above, 0.2 parts of 2,2′-azobisisobutyronitrile was added to the mixture as a polymerization initiator, and the whole was subjected to solution polymerization at 60° C. for 8 hours, thereby providing a solution of an acrylic polymer. The weight average molecular weight of the acrylic polymer was 600,000.
[0193] With respect to 100 parts of the acrylic polymer in the obtained acrylic polymer solution, 20 parts of a terpene-phenol resin (trade name: "YS POLYSTER T-115", softening point: about 115° C., hydroxyl value: 30 mgKOH / g to 60 mgKOH / g, manufactured by Yasuhara Chemical Co., Ltd.) as a tackifier resin, 3 parts of an isocyanate crosslinking agent (trade name: "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.02 parts of an epoxy crosslinking agent (trade name: "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Company, Inc.) as a crosslinking agent, and 6 parts of a product available under the trade name "AT-DN101 BLACK" (manufactured by Dainichiseika Color & Chemicals) as a black pigment were added. Mfg. Co., Ltd.) was added to the solution, and the contents were stirred and mixed to prepare a pressure-sensitive adhesive composition (7).
[0194] The pressure-sensitive adhesive composition (7) was applied to the release surface of a 38 μm thick polyester release liner (trade name: "DIAFOILMRF", manufactured by Mitsubishi Polyester Film, Inc.) and dried at 100°C for 2 minutes to form a pressure-sensitive adhesive layer (7) having a thickness of 87.5 μm.
[0195] [Manufacturing Example 8]: Manufacture of pressure-sensitive adhesive layer (8)
[0196] 93 parts of butyl acrylate (BA), 7 parts of acrylic acid (AA) and 0.05 parts of 4-hydroxybutyl acrylate (4HBA) as monomer components and 233 parts of ethyl acetate as a polymerization solvent were charged into a reaction vessel including a stirrer, a thermometer, a nitrogen introduction tube, a reflux condenser, and a dropping funnel, and stirred for 2 hours while introducing nitrogen into the vessel. After oxygen in the polymerization system had been removed as described above, 0.1 parts of 2,2′-azobisisobutyronitrile was added to the mixture as a polymerization initiator, and the whole was subjected to solution polymerization at 60° C. for 8 hours, thereby providing a solution of an acrylic polymer. The weight average molecular weight of the acrylic polymer was 600,000.
[0197] With respect to 100 parts of the acrylic polymer in the obtained acrylic polymer solution, 20 parts of a terpene-phenol resin (trade name: "YS POLYSTER T-115", softening point: about 115° C., hydroxyl value: 30 mgKOH / g to 60 mgKOH / g, manufactured by Yasuhara Chemical Co., Ltd.) as a tackifier resin, 2 parts of an isocyanate crosslinking agent (trade name: "CORONATE L", 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.02 parts of an epoxy crosslinking agent (trade name: "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Company, Inc.) as a crosslinking agent, and 6 parts of a product available under the trade name "AT-DN101 BLACK" (manufactured by Dainichiseika Color & Chemicals) as a black pigment were added. Mfg. Co., Ltd.) was added to the solution, and the contents were stirred and mixed to prepare a pressure-sensitive adhesive composition (8).
[0198] The pressure-sensitive adhesive composition (8) was applied to the release surface of a 38 μm thick polyester release liner (trade name: "DIAFOILMRF", manufactured by Mitsubishi Polyester Film, Inc.) and dried at 100°C for 2 minutes to form a pressure-sensitive adhesive layer (8) having a thickness of 87.5 μm.
[0199] [Manufacturing Example 9]: Manufacture of pressure-sensitive adhesive layer (9)
[0200] A pressure-sensitive adhesive layer (9) having a thickness of 100.0 μm was formed in the same manner as in Production Example 1 except that the thickness of the final pressure-sensitive adhesive layer was set to 100.0 μm.
[0201] [Manufacturing Example 10]: Manufacture of pressure-sensitive adhesive layer (10)
[0202] 90 parts of butyl acrylate (BA) and 10 parts of acrylic acid (AA) as monomer components and 350 parts of ethyl acetate as a polymerization solvent were charged into a reaction vessel including a stirrer, a thermometer, a nitrogen introduction tube, a reflux condenser, and a dropping funnel, and stirred for 2 hours while introducing nitrogen into the vessel. After oxygen in the polymerization system had been removed as described above, 0.2 parts of 2,2′-azobisisobutyronitrile was added to the mixture as a polymerization initiator, and the whole was subjected to solution polymerization at 60° C. for 8 hours, thereby providing a solution of an acrylic polymer. The weight average molecular weight of the acrylic polymer was 600,000.
[0203] With respect to 100 parts of the acrylic polymer in the obtained acrylic polymer solution, 20 parts of a terpene-phenol resin (trade name: "YS POLYSTER T-115", softening point: about 115° C., hydroxyl value: 30 mgKOH / g to 60 mgKOH / g, manufactured by Yasuhara Chemical Co., Ltd.) as a tackifier resin, 3 parts of an isocyanate crosslinking agent (trade name: "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.02 parts of an epoxy crosslinking agent (trade name: "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Company, Inc.) as a crosslinking agent, and 6 parts of a product available under the trade name "AT-DN101 BLACK" (manufactured by Dainichiseika Color & Chemicals) as a black pigment were added. Mfg. Co., Ltd.) was added to the solution, and the contents were stirred and mixed to prepare a pressure-sensitive adhesive composition (10).
[0204] The pressure-sensitive adhesive composition (10) was applied to the release surface of a 38 μm thick polyester release liner (trade name: "DIAFOILMRF", manufactured by Mitsubishi Polyester Film, Inc.) and dried at 100°C for 2 minutes to form a pressure-sensitive adhesive layer (10) having a thickness of 87.5 μm.
[0205] [Manufacturing Example 11]: Manufacture of pressure-sensitive adhesive layer (11)
[0206] A pressure-sensitive adhesive layer (11) having a thickness of 12.5 μm was formed in the same manner as in Production Example 1 except that the thickness of the final pressure-sensitive adhesive layer was set to 12.5 μm.
[0207] [Manufacturing Example 12]: Manufacture of pressure-sensitive adhesive layer (12)
[0208] A pressure-sensitive adhesive layer (12) having a thickness of 65.0 μm was formed in the same manner as in Production Example 1 except that the thickness of the final pressure-sensitive adhesive layer was set to 65.0 μm.
[0209] [Example 1]
[0210] The side of the pressure-sensitive adhesive layer (1) obtained in Manufacturing Example 1 on which the release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 10 μm) as a substrate layer (1). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (1) having a total thickness of 200 μm (construction: pressure-sensitive adhesive layer (1) / substrate layer (1) / pressure-sensitive adhesive layer (1)) is obtained.
[0211] The evaluation results are shown in Table 1.
[0212] [Example 2]
[0213] The side of the pressure-sensitive adhesive layer (2) obtained in Preparation Example 2 on which a release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 15 μm) as a substrate layer (2). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (2) having a total thickness of 200 μm (construction: pressure-sensitive adhesive layer (2) / substrate layer (2) / pressure-sensitive adhesive layer (2)) is obtained.
[0214] The evaluation results are shown in Table 1.
[0215] [Example 3]
[0216] The side of the pressure-sensitive adhesive layer (3) obtained in Manufacturing Example 3 on which a release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 25 μm) as a substrate layer (3). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (3) having a total thickness of 200 μm (construction: pressure-sensitive adhesive layer (3) / substrate layer (3) / pressure-sensitive adhesive layer (3)) is obtained.
[0217] The evaluation results are shown in Table 1.
[0218] [Example 4]
[0219] The side of the pressure-sensitive adhesive layer (4) obtained in Preparation Example 4 on which the release liner was not provided was attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 40 μm) as a substrate layer (4). The resulting structure was passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner was peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (4) (construction: pressure-sensitive adhesive layer (4) / substrate layer (4) / pressure-sensitive adhesive layer (4)) having a total thickness of 200 μm was obtained.
[0220] The evaluation results are shown in Table 1.
[0221] [Example 5]
[0222] The side of the pressure-sensitive adhesive layer (5) obtained in Production Example 5 on which the release liner was not provided was attached to each of the two surfaces of a polycarbonate-based polyurethane resin film (manufactured by Nihon Matai Co., Ltd., trade name: "ESMERURS PX90", thickness = 30 μm) as a substrate layer (5). The resulting structure was passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner was peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (5) having a total thickness of 200 μm (construction: pressure-sensitive adhesive layer (5) / substrate layer (5) / pressure-sensitive adhesive layer (5)) was obtained.
[0223] The evaluation results are shown in Table 1.
[0224] [Example 6]
[0225] The side of the pressure-sensitive adhesive layer (5) obtained in Production Example 5 on which the release liner was not provided was adhered to each of the two surfaces of a polyether polyurethane resin film (manufactured by Nihon Matai Co., Ltd., trade name: "ESMER URSET-B", thickness = 30 μm) as a substrate layer (6). The resulting structure was passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner was peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (6) having a total thickness of 200 μm (construction: pressure-sensitive adhesive layer (5) / substrate layer (6) / pressure-sensitive adhesive layer (5)) was obtained.
[0226] The evaluation results are shown in Table 1.
[0227] [Example 7]
[0228] The side of the pressure-sensitive adhesive layer (6) obtained in Preparation Example 6 on which the release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 25 μm) as a substrate layer (3). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (7) having a total thickness of 200 μm is obtained (construction: pressure-sensitive adhesive layer (6) / substrate layer (3) / pressure-sensitive adhesive layer (6)).
[0229] The evaluation results are shown in Table 1.
[0230] [Example 8]
[0231] The side of the pressure-sensitive adhesive layer (7) obtained in Preparation Example 7 on which the release liner was not provided was attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 25 μm) as a substrate layer (3). The resulting structure was passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner was peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (8) having a total thickness of 200 μm was obtained (construction: pressure-sensitive adhesive layer (7) / substrate layer (3) / pressure-sensitive adhesive layer (7)).
[0232] The evaluation results are shown in Table 1.
[0233] [Example 9]
[0234] The side of the pressure-sensitive adhesive layer (8) obtained in Preparation Example 8 on which the release liner was not provided was attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 25 μm) as a substrate layer (3). The resulting structure was passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner was peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (9) (construction: pressure-sensitive adhesive layer (8) / substrate layer (3) / pressure-sensitive adhesive layer (8)) having a total thickness of 200 μm was obtained.
[0235] The evaluation results are shown in Table 1.
[0236] [Comparative Example 1]
[0237] The two pressure-sensitive adhesive layer surfaces on which the release liner was not provided of the pressure-sensitive adhesive layer (9) obtained in Production Example 9 were bonded to each other. The resulting structure was passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner was peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (C1) having a total thickness of 200 μm (configuration: pressure-sensitive adhesive layer (9) / pressure-sensitive adhesive layer (9)) was obtained.
[0238] The evaluation results are shown in Table 1.
[0239] [Comparative Example 2]
[0240] The side of the pressure-sensitive adhesive layer (10) obtained in Preparation Example 10 on which the release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 25 μm) as a substrate layer (3). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (C2) having a total thickness of 200 μm is obtained (construction: pressure-sensitive adhesive layer (10) / substrate layer (3) / pressure-sensitive adhesive layer (10)).
[0241] The evaluation results are shown in Table 1.
[0242] [Comparative Example 3]
[0243] The side of the pressure-sensitive adhesive layer (11) obtained in Preparation Example 11 on which a release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 25 μm) as a substrate layer (3). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (C3) (construction: pressure-sensitive adhesive layer (11) / substrate layer (3) / pressure-sensitive adhesive layer (11)) having a total thickness of 50 μm is obtained.
[0244] The evaluation results are shown in Table 1.
[0245] [Comparative Example 4]
[0246] The side of the pressure-sensitive adhesive layer (12) obtained in Manufacturing Example 12 on which a release liner is not provided is attached to each of the two surfaces of a polyester polyurethane resin film (manufactured by Okura Industrial Co., Ltd., trade name: "SILKLON NES85", thickness = 70 μm) as a substrate layer (C4). The resulting structure is passed through a laminator (0.3 MPa, speed: 0.5 m / min) once at room temperature and then aged in an oven at 50° C. for 1 day. Thereafter, the release liner is peeled off. Thus, as shown in Table 1, a double-sided pressure-sensitive adhesive tape (C4) (construction: pressure-sensitive adhesive layer (12) / substrate layer (C4) / pressure-sensitive adhesive layer (12)) having a total thickness of 200 μm is obtained.
[0247] The evaluation results are shown in Table 1.
[0248]
[0249]
[0250] The double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention can be suitably used for the interior of a mobile device, etc. The double-sided pressure-sensitive adhesive tape according to at least one embodiment of the present invention is typically used for fixing electronic device members.
[0251] According to at least one embodiment of the present invention, a double-sided pressure-sensitive adhesive tape that can exhibit all of excellent impact resistance, excellent reworkability, and excellent alcohol resistance can be provided.
Claims
1. A double-sided pressure-sensitive adhesive tape comprising: substrate layer; and pressure-sensitive adhesive layers disposed on both sides of the substrate layer, The base material layer is formed of a resin film containing a polyurethane-based resin as a main component, wherein the pressure-sensitive adhesive layers are each formed of a pressure-sensitive adhesive composition, wherein the pressure-sensitive adhesive composition comprises at least one selected from the group consisting of a monomer component (m) and a polymer component (P) obtained by polymerizing the monomer component (m), wherein the monomer component (m) comprises 91 wt % or more of butyl (meth)acrylate, wherein the ratio of the thickness of the substrate layer to the total thickness of the double-sided pressure-sensitive adhesive tape is 3% to 13%, and wherein the double-sided pressure-sensitive adhesive tape has a force of 30 N / m to 150 N / m at 100% strain at 23° C. and 50% RH, The double-sided pressure-sensitive adhesive tape has a total thickness of 100 μm or more. 2 . The double-sided pressure-sensitive adhesive tape according to claim 1 , wherein the monomer component (m) comprises 91 wt % to 99 wt % of butyl (meth)acrylate. 3 . The double-sided pressure-sensitive adhesive tape according to claim 1 , wherein the monomer component (m) comprises 1 wt % to 8 wt % of (meth)acrylic acid. 4 . The double-sided pressure-sensitive adhesive tape according to claim 1 , wherein the double-sided pressure-sensitive adhesive tape is used for fixing electronic device members.
Citation Information
Patent Citations
Double-sided adhesive sheet
JP2015120876A
Double-sided pressure-sensitive adhesive tape
CN103242750A
Adhesive double coated tape for fixing abrasive, and adhesive tape with the abrasive
JP2010194699A
Double-sided adhesive sheet
JP2013075999A
Pressure-sensitive adhesive sheet for portable electronics
US20170158918A1